Challenges in Spine: Management of Spinal Infections. A Flow-Chart to Guide Decision Making. Issue 1 (April 2016) - Gasbarrini, Alessandro; Ghermandi, Riccardo; Girolami, Marco; Bandiera, Stefano; Brodano, Giovanni Barbanti; Terzi, Silvia; Babbi, Lisa; Boriani, Stefano
Introduction: Spinal infections are rare diseases, whose management highlights the importance of a multidisciplinary approach. Although treatment is based on antibiotics, always selected on coltural and antibiogram tests, surgery is required in case of development of spinal instability or deformity, progressive neurological deficits, drainage of abscesses, or failure of medical treatment. The first step of the algorithm is diagnosis, which is established on MRI with contrast, PET/CT scan, blood tests (CRP and ESR) and CT-guided needle biopsy. Evaluation of response to the specific antibiotic therapy is based on variations in Maximum Standardized Uptake Value (SUVmax) after 2 to 4 weeks of treatment. In selected cases, early minimally invasive surgery was proposed to provide immediate stability and avoid bed-rest. Material and Methods: From 1997 to 2014, 182 patients affected by spinal infections have been treated at the same institution (Istituto Ortopedico Rizzoli – Bologna, Italy) according to the proposed algorithm. Mean age was 56 years (range 1 - 88). Male to female ratio was 1, 46. Results: Minimum follow-up was 1 year. Infections were mostly located in the lumbar spine (57%) followed by thoracic (37%) and cervical spine (6%). Conservative treatment based on antibiotics needed surgery (open and/or percuteneous minimally invasive) as an adjuvant in 83 patients out of 182 (46%). Conclusion: Management of spinal infections still remains a challenge in spinal surgery and multisciplinary approach is mandatory. This algorithm represents the shared decision making process from diagnosis to the most appropriate treatment, led to successful outcomes with a low-complication rate.